Survival among Breast Cancer Patients in a Tertiary Cancer Center in Brunei Darussalam - B., Eclarinal; R., Patnaik (Journal of Breast Cancer Survival, 2020)
Background In Brunei Darussalam, cancer has been the leading cause of death, and breast cancer as the leading cause of death among women. With a nationally-funded cancer treatment, it is essential to determine the survival rates among breast cancer patients which can serve as a basis for comparison across timelines with the end view of improving healthcare delivery, hence, survival among the patient population. Methods This study was conducted from January – May 2019. Medical records data were abstracted for breast cancer patients treated between years 2011-2016 in a tertiary specialist cancer center. Kaplan-Meier Product Limit estimation was used for the over-all observed survival rates within 5 years after diagnosis. STATA Version 15 was used for statistical analysis. Ethical approval was obtained. Results Over-all, five-year breast cancer survival rates was favorable at 88.89%. . Survival rates according to TNM staging showed lowest at stage IV at 59% five-year survival. Survival rates according to age at the time of diagnosis showed favorable survival across age groups except for age groups 30-39 years and 80 years old and above. Survival rates according to treatment combinations were highest in surgery (mastectomy) and hormonal therapy. Conclusions The Center’s 5-year breast cancer survival rates were relatively high and comparable to survival figures of developed countries. The Center’s high survival rates could have been related to the ‘treatment factors’ due to the following: prompt treatment of early stage breast cancer stages, responsive coordination, government-funded cancer treatment which allowed patients uninterrupted, free access to standard treatment.
Keywords: survival rates; breast cancer